Analysis of the zonal and rectangular slots on a conducting spherical cavity. - Kwok Wa Leung (IEEE Transactions on antennas and propagation)
The zonal slot cut on a conducting spherical cavity is analyzed rigorously. The slot is excited asymmetrically, which excites higher order azimuthal modes. The Green's function approach is used to formulate an integral equation for the magnetic current in the slot, which is solved using the moment method (MoM). New recurrence formulas are derived so that within their stable region the admittance integrals can be evaluated without the need for any numerical integration. In this case, the solution is very easy to implement with extremely short computation time. The effects of the latitude angle on the peak resistance and percentage bandwidth are investigated. Furthermore, the cavity resonance modes and their degeneracy are examined by plotting the expansion coefficients of the magnetic current. In addition, the problem of a rectangular slot in the nonequatorial plane is also studied. Measurements are carried out and good agreement between theory and experiment is obtained